Perception, attention, and working memory are disproportionately impaired in dementia with Lewy bodies compared with Alzheimer's disease. Issue 2 (1st February 2001) - Calderon, J; Perry, R J; Erzinclioglu, S W; Berrios, G E; Dening, T R; Hodges, J R
Abstract : OBJECTIVE: To test the hypotheses that visuoperceptual and attentional ability are disproportionately impaired in patients having dementia with Lewy Bodies (DLB) compared with Alzheimer's disease (AD). METHODS: A comprehensive battery of neuropsychological tasks designed to assess working, episodic, and semantic memory, and visuoperceptual and attentional functions was given to groups of patients with DLB (n=10) and AD (n=9), matched for age, education, and mini mental state examination (MMSE), and to normal controls (n=17). RESULTS: Both patient groups performed equally poorly on tests of episodic and semantic memory with the exception of immediate and delayed story recall, which was worse in the AD group. Digit span was by contrast spared in AD. The most striking differences were on tests of visuoperceptual/spatial ability and attention. Whereas patients with AD performed normally on several subtests of the visual object and space perception battery, the DLB group showed substantial impairments. In keeping with previous studies, the AD group showed deficits in selective attention and set shifting, but patients with DLB were more impaired on virtually every test of attention with deficits in sustained, selective, and divided attention. CONCLUSIONS: Patients with DLB have substantially greater impairment of attention, working memory, and visuoperceptual ability than patients with AD matched for overall dementia severity. Semantic memory seems to be equally affected in DLB and AD, unlike episodic memory, which is worse in AD. These findings may have relevance for our understanding of the genesis of visual hallucinations, and the differential diagnosis of AD and DLB.